Development of a questionnaire to determine the case detection delay of leprosy: A mixed-methods cultural validation study. - Naomi D de Bruijne; Kedir Urgesa; Abraham Aseffa; Kidist Bobosha; Anne Schoenmakers; Robin van Wijk; Thomas Hambridge; Mitzi M Waltz; Christa Kasang; Liesbeth Mieras (Public Library of Science (PLoS), 2022)
Background Delay in case detection is a risk factor for developing leprosy-related impairments, leading to disability and stigma. The objective of this study was to develop a questionnaire to determine the leprosy case detection delay, defined as the period between the first signs of the disease and the moment of diagnosis, calculated in total number of months. The instrument was developed as part of the PEP4LEP project, a large-scale intervention study which determines the most effective way to implement integrated skin screening and leprosy post-exposure prophylaxis with a single-dose of rifampicin (SDR-PEP) administration in Ethiopia, Mozambique and Tanzania. Methodology/principal findings A literature review was conducted and leprosy experts were consulted. The first draft of the questionnaire was developed in Ethiopia by exploring conceptual understanding, item relevance and operational suitability. Then, the first draft of the tool was piloted in Ethiopia, Mozambique and Tanzania. The outcome is a questionnaire comprising nine questions to determine the case detection delay and two annexes for ease of administration: a local calendar to translate the patient's indication of time to number of months and a set of pictures of the signs of leprosy. In addition, a body map was included to locate the signs. A 'Question-by-Question Guide' was added to the package, to provide support in the administration of the questionnaire. The materials will be made available in English, Oromiffa (Afaan Oromo), Portuguese and Swahili via https://www.infolep.org. Conclusions/significance It was concluded that the developed case detection delay questionnaire can be administered quickly and easily by health workers, while not inconveniencing the patient. The instrument has promising potential for use in future leprosy research. It is recommended that the tool is further validated, also in other regions or countries, to ensure cultural validity and to examine psychometric properties like test-retest reliability and interrater reliability.